Local Wisdom-Based Water Resources Conservation: Enhancing Local Wisdom in Society 5.0 - Aspan, Zulkifli; Widodo, Ernu; Jurdi, Fajlurrahman; Jundiani, Jundiani (Hasanuddin Law Review, 2023)
Local wisdom as capital for sustainable water resource conservation is becoming increasingly important in the era of Society 5.0. It is characterized by technological transformation and extensive interconnection. In this context, implementing local wisdom values in the conservation of water resources is a significant challenge. This paper discusses the challenges faced in conserving sustainable local wisdom-based water resources in the era of Society 5.0, such as cultural and technological changes. This paper also examines legal regulations in water resource conservation based on local wisdom, such as how laws regulate water use and budget arrangements for water resource conservation. The method used is a literature study of several legal materials using concept and statutory approaches, then analyzed to answer the problems studied. The results show that it is necessary to strengthen the recognition and protection of local wisdom through the preparation or revision of laws and regulations that recognize the values of local wisdom in the conservation of water resources, a collaboration between stakeholders to build citizen communication and consultation; and regulatory adjustments to support the conservation of water resources in the era of society 5.0.